The Role of Inpatient Room Physical Design in Supporting the Quality of Health Services: A Case Study at Hospital X - Saputri, Giovany Okvia; Rusdi, Achmad Jaelani; Suhariyono, Untung Slamet; Ma'roef, Moch. Noer Hoedan (PROMOTOR, 2025)
This study aims to analyze the effect of inpatient room plans on the quality of nursing services at Hospital X, Blitar Regency. The background of this study is based on the change in the layout of the inpatient room after the functioning of the new building in the hospital, which causes confusion for patients and families due to information plans that are no longer in accordance with the actual conditions. This study uses a qualitative approach through observation, interviews, and open discussions with hospital technical staff. The results showed that unupdated spatial plans inhibited the effectiveness of nurses' work and decreased patient satisfaction. As a solution, the researchers designed a new plan that was more informative, easily accessible on social media, and placed in strategic areas of the hospital. The plan is expected to improve the flow of movement, support coordination between staff, and improve the quality of nursing services. Recommendations from this study include regular updates of the plan, the use of information technology, training of information officers, and the involvement of users in the evaluation of the plan.